3-DIMENSIONAL SIMULATION AND FEASIBILITY STUDY OF BIOMASS/COAL CO-COMBUSTION BURNER - Nataliya DUNAYEVSKA (Stefan cel Mare University of Suceava, 2017)
Combustion of solid biomass mixed with coal in existing boilers not only reduces harmful emissions, but also allows diversifying the available fuel base. Such technology allows to implement the efficient use of food industry solid wastes, which otherwise would be dumped in piles, and thus produce harmful environmental impact. The geometrical models of research reactor and a burner thermal preprocessing of pulverized coal were developed and calculational meshes were generated. The geometrical model of the VGP-100Vpresents only fluid domain whereas the effect of cooled walls was substituted by the equivalent biudary conditions deruved on the basis of direct experimentation. The model of the VGP-100V allowed accounting for the specifics of radiative heat transfer by comparison of experimental thermo-couple measurements to the simulated by the model one. A model has been developed allowing the determination of actual temperatures of combustion gases flow based upon the reading of unsheathed thermo-couples by taking into account the reradiation of the thermo-couple beads to the channel walls. Based on the ANSYS 3-D process model in the burner of the Trypilska Thermal Power Plant (TPP) for the combustion of low-reactive coal with the thermochemical preparation of the design of an actual burner has been developed. On the basis of the experimental studies of the actual burner and the above-mentioned CFD calculations, the burner draft of the 65 MW for TPP-210A boiler aimed at the implementation of biomass-coal co-combustion was designed.